PENDAMPINGAN SOSIALISASI NEW NORMAL SEBAGAI UPAYA MENGHADAPI COVID-19 PADA TEMPAT WISATA PRECET FOREST PARK - Agung Bagaskoro; Muhamad Shaehul Sopyan; Alqomatul Lailiyah; Amelia Amelia; Safinatun Najah (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2021)
Purpose of the study: preventing the spread of the COVID-19 virus as well as efforts to improve the quality of the village environment, as well as making efforts to preserve the Precet Forestpark tourist attractions in Sumbersuko Village so that they can return to being well-maintained tourist attractions. Methodology: In this assistance, the first thing to do is to analyze the strengths and weaknesses contained in the object of service. Next is socialization and education as well as monitoring. Main Findings: Prior to Mentoring, it is hoped that the Precet Forest Park tourism in Sumbersuko Village, Wagir District, Malang Regency can maintain its beauty and of course in terms of cleanliness. Applications of this study: the formation of clean and healthy living habits and provide additional insight. Novelty/Originality of this study: In this service, we have been able to identify the problems experienced by the company owner, especially the problem of human resources or the ability of marketers to market a product.